Uji Vitamin C Dan Mutu Organoleptik Kimchi Pakcoy (Brassica rapa Subsp.Chinensis) Terhadap Pengaruh Konsentrasi Garam Dan Lama Fermentasi - Fizzaria Khasbullah; Windu Mangiring; Krisnarini Krisnarini (JURNAL WACANA PERTANIAN, 2020)
Kimchi is a food that has a distinctive taste, which is sour due to the fermentation process. Kimchi made from vegetables and various spices in the form of spices. This research is about salt concentration and fermentation time on vitamin C content and organoleptic quality of kimchi pakcoy. The research method used is the method of description (single factor; two replications) by presenting the results of observations in the form of a histogram, then discussed descriptively. The treatment factor is a combination of salt concentration and fermentation time. Salt concentration (K) which consists of 3 levels, namely: K1 (2%), K2 (4%) and K3 (6%) and the duration of fermentation (L) which consists of 3 levels, namely: L1 (2 days), L2 (4 days) and L3 (6 days). The parameters analyzed were vitamin C content and organoleptic quality related to taste, aroma, color and texture. Salt concentration and fermentation time greatly affect the content of vitamin C and organoleptic quality. The highest vitamin C content was found in the K3L3 sample, namely 6% salt concentration and 6 days of fermentation time with a vitamin C content of 0.7320 mg / gr. Organoleptic quality using the hedonic test, related to taste, aroma, color and texture, yielded successive values, namely 5.2 (K3L2); 5,6 (K2L3); 5.9 (K1L1); 6.1 (K1L1)